UPAYA PENINGKATAN KEMAMPUAN PASSING BAWAH MELALUI METODE PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) - Purwodiharjo, Priyangga; Sri Sumartiningsih; Agus Yuwono; Bambang Subali; Edi Waluyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to evaluate the effectiveness of teaching underhand passing in volleyball through the Team Game Tournament (TGT) approach. The research, conducted as Classroom Action Research (CAR), employed a quantitative method and was carried out at the high school level. A total of 36 students participated in the study, consisting of 16 male and 20 female students. Before the intervention, initial data showed that only 13 students (37%) achieved learning mastery. After the implementation of the TGT teaching model in the first cycle, learning mastery improved to 17 students (47%). In the second cycle, the application of the same method resulted in a significant improvement, with 33 students (92%) achieving learning mastery. These findings indicate that the TGT teaching method effectively enhances students' learning outcomes, particularly in mastering underhand passing in volleyball.